Integration of IoT Technologies and High-Performance Phenotyping for Climate Control in Greenhouses and Mitigation of Water Deficit: A Study of High-Andean Oat - Edwin Villagran; Gabriela Toro-Tobón; Fabián Andrés Velázquez; German A. Estrada-Bonilla (AgriEngineering)
Climate change has intensified droughts, severely impacting crops like oats and highlighting the need for effective adaptation strategies. In this context, the implementation of IoT-based climate control systems in greenhouses emerges as a promising solution for optimizing microclimates. These systems allow for the precise monitoring and adjustment of critical variables such as temperature, humidity, vapor pressure deficit (VPD), and photosynthetically active radiation (PAR), ensuring optimal conditions for crop growth. During the experiment, the average daytime temperature was 22.6 °C and the nighttime temperature was 15.7 °C. The average relative humidity was 60%, with a VPD of 0.46 kPa during the day and 1.26 kPa at night, while the PAR reached an average of 267 μmol m−2 s−1. Additionally, the use of high-throughput gravimetric phenotyping platforms enabled precise data collection on the plant–soil–atmosphere relationship, providing exhaustive control over water balance and irrigation. This facilitated the evaluation of the physiological response of plants to abiotic stress. Inoculation with microbial consortia (PGPB) was used as a tool to mitigate water stress. In this 69-day study, irrigation was suspended in specific treatments to simulate drought, and it was observed that inoculated plants maintained chlorophyll b and carotenoid levels akin to those of irrigated plants, indicating greater tolerance to water deficit. These plants also exhibited greater efficiency in dissipating light energy and rapid recovery after rehydration. The results underscore the potential of combining IoT monitoring technologies, advanced phenotyping platforms, and microbial consortia to enhance crop resilience to climate change.